"To Spin or Not to Spin?"—Is Spin‐Coating the Ideal Technique for Pre‐Deposition of Sodium Fluoride for CIGS Rear Surface Passivated Ultrathin Solar Cells?. Issue 10 (17th March 2022) - Birant, Gizem; de Wild, Jessica; Meuris, Marc; Poortmans, Jef; Vermang, Bart
Abstract : Herein, using the spin‐coating process as a sodium pre‐deposition technique for Cu(In, Ga)Se2, ultrathin film solar cells is discussed. Throughout this study, several challenges are detected to overcome, such as unevenly deposited salt layers and unplanned clusters (even islands) of sodium salts due to accumulation. The solar cell performances with the optimal and nonoptimal amounts of sodium are shared to assess the effect of varying sodium amounts on performance. The hyperspectral photoluminescence (PL) mapping and imaging and reflection measurements are also used to emphasize the importance of homogeneity of the sodium layer. Abstract : An unexpected error in spin‐coating sodium fluoride (NaF) solution onto aluminum oxide rear surface passivation layer results in optimal and nonoptimal amounts of NaF deposited in the same sample. It causes significant differences in solar cell performances of ultrathin Cu, (In, Ga), Se2 solar cells. The inhomogeneity is determined by hyperspectral imaging and supported by scanning electron microscope (SEM).